The dissimilar twins - a comparative, site-selective in situ study of CO adsorption and desorption on Pt(3 2 2) and Pt(3 5 5) - Tränkenschuh, Barbara; Papp, Christian; Fuhrmann, Thomas; Denecke, Reinhard; Steinrück, Hans-Peter (Surface Science, 2007)
The adsorption and desorption of CO on stepped Pt(3 2 2) = Pt(S)-[5(1 1 1) × (1 0 0)] and Pt(3 5 5) = Pt(S)-[5(1 1 1) × (1 1 1)] were investigated using in situ high-resolution X-ray photoelectron spectroscopy at BESSY II, which allows to clearly distinguish between different step and terrace adsorption sites. For the two surfaces, with the same nominal terrace width of five atomic rows, but different step orientation, significant differences are observed. While for Pt(3 5 5) CO adsorption at steps only occurs at on-top sites, on Pt(3 2 2) both step on-top and bridge sites are occupied, albeit with a significantly lower coverage (0.07 vs. 0.13 ML at 200 K). On both surfaces terrace sites are only occupied when the step sites are almost saturated confirming the enhanced binding energy at step sites. CO adsorbed at the (1 1 1) steps on Pt(3 5 5) is more strongly bound than on the (1 0 0) steps on Pt(3 2 2), which is attributed to the different electronic and geometric structure of the steps. The relative occupation of terrace and step sites at a given coverage remains the same between 120 and 290 K on Pt(3 5 5) K, but shows major changes on Pt(3 2 2), between step on-top and bridge sites as well as terrace on-top and bridge sites. On Pt(3 5 5) a smaller CO terrace coverage is found (0.36 vs. 0.40 ML on Pt(3 2 2) at 200 K), mainly due to the lower occupation of terrace bridge sites. For Pt(3 2 2), an ordered adsorbate phase is deduced from a c(4 × 2)-like LEED pattern, which indicates adsorbate order beyond the extension of a single terrace. A model for this structure is proposed. © 2006 Elsevier B.V. All rights reserved.